2013
DOI: 10.1177/1947601913481670
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of HIF-1  and Notch3 Is Required for the Expression of Carbonic Anhydrase 9 in Breast Carcinoma Cells

Abstract: Expression of carbonic anhydrase 9 (CA9) is associated with poor prognosis and increased tumor aggressiveness and does not always correlate with HIF-1α expression. Presently, we analyzed the regulation of CA9 expression during hypoxia by HIF-1α, Notch3, and the von Hippel-Lindau (VHL) in breast carcinoma cells. Both HIF-1α and Notch3 were absolutely required for the expression of CA9 mRNA, protein, and reporter. Reciprocal coimmunoprecipitation of HIF-1α, Notch3 intracellular domain (NICD3), and pVHL demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 55 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…Coexpression of the Wnt receptor-Frizzled receptor 6, with HIF1/2α in hypoxic areas of primary human neuroblastomas tumors is characteristic of a population of rare, highly tumorigenic stem-like cells [42]. Interaction of HIF-1α and Notch3, which is required for the expression of the hypoxia-responsive gene Carbonic Anhydrase 9, is a potential target for cancer/stem cell therapy [43]. The HIF1α-Notch pathway is proposed to be essential for maintenance of CSCs in hematological malignancies under conditions of normoxia [44].…”
Section: Discussionmentioning
confidence: 99%
“…Coexpression of the Wnt receptor-Frizzled receptor 6, with HIF1/2α in hypoxic areas of primary human neuroblastomas tumors is characteristic of a population of rare, highly tumorigenic stem-like cells [42]. Interaction of HIF-1α and Notch3, which is required for the expression of the hypoxia-responsive gene Carbonic Anhydrase 9, is a potential target for cancer/stem cell therapy [43]. The HIF1α-Notch pathway is proposed to be essential for maintenance of CSCs in hematological malignancies under conditions of normoxia [44].…”
Section: Discussionmentioning
confidence: 99%
“…IL6 increases Notch3 through the microtubule associated protein kinase (MAPK) pathway that leads to mammosphere formation and increase of Carbonic anhydrase 9 (CA‐IX), an enzyme involved in survival during hypoxia . Notch3 is activated during hypoxia in prostate cancer cells, and Notch3‐Hypoxia‐inducible factor 1‐alpha (HIF‐1α) interaction is necessary for induction of CA‐IX in breast carcinoma cells . Notch3‐HIF‐1α interaction has also been found to be important in hypoxia‐related radiation resistance in lung cancer .…”
Section: Notch3 In Hypoxia and Inflammationmentioning
confidence: 99%
“…The essential role of Notch3 in reversal of tamoxifen‐induced mitochondrial toxicity was demonstrated when IL6 treatment failed to increase mitochondrial activity in Notch3 knockdown cells . Several studies have reported that in metastatic breast cancer, functional Notch3 is essential for IL6 to maintain high levels of carbonic anhydrase, an enzyme associated with hypoxia survival and cancer invasiveness .…”
Section: Breast Cancermentioning
confidence: 99%
“…Essentially, transcription of the CA9 gene is induced by binding of HIF-1α to the hypoxia-responsive element in the core promoter of CA9 [10]. However, at least in breast cancer, the expression of CAIX was found to be dependent on the interaction between HIF-1α and Notch3 intracellular domain, thus suggesting that Notch3 signalling may serve as a link between the regulation of hypoxia response and the maintenance of stem cell phenotype [11]. Furthermore, CAIX expression in cancers can be induced by the hypomethylation of the CA9 promoter or by inactivating mutations in the VHL gene that may drive the overexpression of CAIX independently of hypoxic conditions [12][13][14].…”
Section: Introductionmentioning
confidence: 99%